The police role in preventing homicide: considering the impact of problem-oriented policing on the prevalence of murder - Goldkamp, John S.; Fyfe, James J.; Campbell, Suzanne P. (Journal of research in crime and delinquency, 2003)
Criminal justice practitioners and scholars have traditionally held that homicide is relatively immune from police suppression efforts. Recently, the widespread adoption of community and problem-oriented policing and concomitant decreases in violent crime have raised questions about what the police can reasonably be expected to accomplish. This article examines a joint effort by the Bureau of Justice Assistance and the city of Richmond, California, to apply the lessons of problem-oriented policing to homicide work. Analyses of Richmond homicides from 1985 to 1998 suggest that the nature and pattern of murders changed notably following adoption of the new policing philosophy, and interrupted time-series analysis with homicide data from 75 other California cities suggests the changes in Richmond were unique. Results indicate that homicide prevention is a critical police responsibility and that by employing problem-oriented strategies and garnering citizen involvement, police may be able to effectively reduce the prevalence of such violence